The role of motilin in periodic interdigestive pancreatic secretion in dogs. - Magee, D F (1984)
The role of motilin in the periodic interdigestive secretion of the pancreas was studied in conscious dogs, each with a chronic gastric fistula, a Heidenhain pouch and a Thomas duodenal fistula. Motilin increased pancreatic water, bicarbonate and protein secretion and the motility of the stomach, duodenum and Heidenhain pouch in a manner which closely resembles the spontaneous changes which occur during interdigestive activity. Endogenous motilin released by duodenal alkalinization had the same effect as exogenous hormone. Continuous infusion of motilin did not cause continuous pancreatic secretion and gut motility but merely shortened the interval of the periodic interdigestive activity. Exogenous and endogenous motilin were ineffective following atropine. Hexamethonium abolished the pancreatic and duodenal peaks but not the changes in gastric and pouch motility induced by motilin or duodenal alkalinization.